PEMBELAJARAN MORAL MELALUI MOVIE LEARNING “BATTLE OF SURABAYA” PADA SISWA SD - Marwan, Iwan; badrus, moh; Siti Fadhilah, Asna (Dialektika: Jurnal Bahasa, Sastra, dan Pendidikan Bahasa dan Sastra Indonesia, 2024)
This study aims to describe Moral Learning in the Battle of Surabaya Film in Class V Students at SDN Plosorejo 1, Gampengrejo District, Kediri Regency by Aryanto Yuniawan. Specifically, it includes: 1) What are the values of moral learning in the movie learning “Battle Of Surabaya “and 2) What are the implications of the movie learning “Battle Of Surabaya “for the moral learning of fifth grade students at SDN Plosorejo 1.This type of research is library research (Library Research). The primary data source is the film "Battle Of Surabaya" while the secondary data is obtained from books, journals and articles related to the film. Data collection techniques used are documentation and observation. In terms of data validity, persistence techniques and data analysis using content analysis.The results of the study show that the film "Battle Of Surabaya" is a film capable of being a source or medium for moral learning. The value of moral learning in the film "Battle Of Surabaya", this is indicated by the existence of: 1) There are several moral learning values of responsibility, caring, honesty and patience. 2) The values of moral learning in the film "Battle Of Surabaya" are also relevant to the values of moral learning in school life. Namely the attitude of responsibility towards completing the assigned task, caring for friends who are having difficulties, being honest in speaking, and being patient in facing tests and existing problems.